FACTORS CORRELATED TO THE OCCURRENCE OF ANEMIA IN TRIMESTER III PREGNANT MOTHERS IN THE WORK AREA OF KASSIKASSI PUBLIC HEALTH CENTER OF MAKASSAR CITY - Hayati Anwar (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction : Prevalence of anemia in the world is very high especially in the developing countries including Indonesia. Anemia in pregnancy is a mother condition with hemoglobin level under 11 gr of trimester I and trimester Ill or hemoglobin level 10.5 gr of trimester II. Anemia in pregnancy can have a bad affect especially at the time of pregnancy and childbirth. The research aims to determine the factors correlated to the occurrence of anemia in trimester IIl pregnant mothers in the work area of Kassi-Kassi Public Health Center of Makassar City. Method : The research was an analytic observational study with cross sectional approach. The populations were all pregnant mothers in the work area of KassiKassi Public health Center of Makassar. The sample consisted of 45 trimester pregnant women selected using total sampling method. The data consisted of primary and secondary data. They were analyzed using chi-square statistic test. Result : The results of the research indicate that of the 45 respondents, 23 (51.1%) of them has anemia. The variables correlated to trimester pregnant women are socio-economy (p=0.000), distance of pregnancy (p=0.000), and obedience of taking tablet Fe (p=000). Conclusion : Increase the obedience to take tablet Fe, to consume food containing enough iron, to set the gestational distance, to improve knowledge by making use of face-to-face opportunity in public health center, and to use existing media. It is necessary to control nutrient status and Fe tablet in accordance with suggestion.